The determinants of the use of assistants at surgery - Trude, Sally; Rand eBooks (Santa Monica, CA : RAND, 1990)
This Note examines the factors that influence the use of physicians as assistants at surgery. Its goal is to describe general patterns of use, as well as to identify potentially inappropriate uses. The author found that most of the assistant-at-surgery dollars are spent on only a small number of procedures. The author therefore found no other procedures for which requiring prior approval could provide savings comparable to those for cataract procedures. Additional analyses show that 86 percent of the uses of physicians as assistants at surgery occur in inpatient hospitals. A striking regional effect emerged from the analysis--physicians in the Mountain and Pacific regions are more than twice as likely to use a physician as an assistant at surgery as are physicians in other parts of the country. This regional effect remains even after controlling for teaching hospitals, urban/rural status, and other characteristics of the physician and the patient.
"February 1990."
"RAND/UCLA/Harvard Center for Health Care Financing Policy Research."
Includes bibliographical references (p. 73).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Medical care, Cost of -- United States; Surgery -- Economic aspects -- United States; Surgery -- Economic aspects; Surgery -- Practice -- United States; Cost-Benefit Analysis; Medicare Part B -- economics -- United States; Surgery -- manpower; Surgical Procedures, Operative -- economics -- United States; Electronic books